In Vitro Evaluation of the Cytotoxic Potential of Environmental Contaminant Mixtures Present in Water for Human Use - Israa J. Hakeem; Ngiste Amare (Adsorption Science & Technology)
Chemicals from Pharmaceuticals and Personal Care Products (PPCPs) have become much more prevalent in the environment in recent years. The effects of these substances on human health and the environment are frequently debatable because they typically have poorly understood mechanisms of toxic action. For this reason, we set out to evaluate a binary mixture consisting of butylhydroxyanisole (BHA) and propylparaben (PPB), two approved additives that have been found in the environment and have a range of health-related effects. Based on our prior research, we chose an experimental model called Vero cells, kidney fibroblasts from the African green monkey (Chlorocebus aethiops), with high sensitivity in toxicology studies and ideal characteristics for the analysis of chemical compounds’ mechanisms of action. The experimental design includes a battery of tests using many complimentary biochemical and morphological biomarkers, the usefulness of which we have previously established. The outcomes demonstrated that the mixtures of BHA and PPB cause significant functional alterations brought on by osmotic imbalance, which are connected to irregularities in cell cycle progression, increases in ploidy, which included cell cycle imbalances as well as increases in proliferation. On the other hand, we have been able to show that the quantitative estimate of the anticipated cellular responses generally does not adjust precisely to the observed effect through the analysis of the prediction of the combined effect using mathematical models. However, once the individual compounds’ respective mechanisms of action have been established, the toxicity caused by the mixtures can be qualitatively predicted.